High-temperature proton exchange membrane based on silica cross-linked polybenzimidazole and preparation method of high-temperature proton exchange membrane
By introducing silicon-oxygen cross-linked mesh structure into polybenzimidazole, the problems of insufficient proton conduction capacity and low mechanical properties in proton exchange membrane fuel cells are solved, and high mechanical properties, antioxidant properties and phosphoric acid retention are improved, extending the service life of the membrane.
Patent Information
- Application Number
- CN202411768133.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
AI Technical Summary
In existing proton exchange membrane fuel cells, polybenzimidazole (PBI) has insufficient proton conduction ability, and phosphoric acid doping will reduce the mechanical properties and phosphoric acid retention of the membrane, affecting the battery performance and life.
By polymerizing 3,3'-diaminobenzidine, 4,4'-diphenyl ether dicarboxylic acid and 5-hydroxy isophthalic acid to form a polybenzimidazole backbone containing ether bonds and phenolic hydroxyl groups, and grafting a silane coupling agent on the backbone to form a silicon oxygen cross-linked network structure, improving the mechanical properties and antioxidant properties of the film.
It improves the mechanical properties, antioxidant properties and acid resistance of the proton exchange membrane, reduces the swelling rate and the loss of phosphoric acid, and extends the service life of the membrane.
Smart Images

Figure CN119695217A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-temperature proton exchange membrane, in particular to a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole and a preparation method thereof. Background Art
[0002] A proton exchange membrane fuel cell is an energy conversion device that can convert the chemical energy in hydrogen into electrical energy. The proton exchange membrane (PEM) is the core component of the proton exchange membrane fuel cell, which prevents the gas from mixing between the anode channel and the cathode channel and transfers protons from the anode to the cathode.
[0003] Polybenzimidazole (PBI) has been widely studied for its excellent thermal stability and good mechanical properties. PBI itself has very weak proton conductivity. In order to meet the requirements of use in proton exchange membrane fuel cells, its proton conductivity needs to be improved. Doping with phosphoric acid (PA) to prepare PBI / PA composite membranes is a commonly used method to improve the conductivity of proton exchange membranes. Generally, the greater the amount of PA doping, the higher the conductivity of the proton exchange membrane. However, the doping of PA will reduce the mechanical properties of the PBI membrane, further affecting the performance and life of the proton exchange membrane and fuel cell. In addition, the retention rate of PA in the membrane also needs to be improved. PA will leak out of the membrane, causing the conductivity of the membrane to decrease. Therefore, the development of a PBI composite proton exchange membrane with high acid absorption rate, high mechanical properties and high phosphoric acid retention rate is of great significance to promote the development of fuel cells. Summary of the invention
[0004] First, 3,3'-diaminobenzidine (DAB), 4,4'-diphenyl ether dicarboxylic acid (OBBA) and 5-hydroxyisophthalic acid (OHIPA) are polymerized to form a polybenzimidazole main chain containing ether bonds and phenolic hydroxyl groups, and then a silane coupling agent is grafted onto the polybenzimidazole main chain. Finally, film formation and acid catalysis are performed to obtain a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole. The embedding of hydroxyl functional groups can provide grafting sites for the cross-linking agent. The introduction of a silicon-oxygen cross-linked network structure into polybenzimidazole can improve the mechanical properties, antioxidant properties and acid resistance of the membrane, and can also reduce the swelling rate of the proton exchange membrane.
[0005] The preparation method of the high temperature phosphoric acid proton exchange membrane is as follows:
[0006] (1) Preparation of PBI containing ether bonds and phenolic hydroxyl functional groups
[0007] In a nitrogen atmosphere, DAB and P were heated at 100°C. 2 O 5, OBBA and OHIPA are dissolved in polyphosphoric acid (PPA) in sequence. After the drugs are completely dissolved, the temperature is raised to 160°C for prepolymerization for 3 hours, and the solution is polymerized at 200°C until the solution climbs. The temperature is lowered to 70°C, phosphoric acid is added to hydrolyze the phosphate ester, and the polymer solution is poured into deionized water to precipitate solids. Wash with boiling water 4-5 times until the pH of the washing solution is neutral, and bake at 80°C for 24 hours to obtain PBI containing ether bonds and phenolic hydroxyl functional groups, named OPBI-OHX, X is the total molar percentage of OHIPA to OBBA and OHIPA, 0<X<50;
[0008] The molar ratio of 3,3'-diaminobenzidine to the total molar ratio of 4,4'-diphenylether dicarboxylic acid and 5-hydroxyisophthalic acid is 1:1.
[0009] The mass of phosphorus pentoxide is 8-15% of the mass of polyphosphoric acid.
[0010] (2) Formation of silicon-oxygen network structure
[0011] Under nitrogen atmosphere, OPBI-OHX and silane coupling agent were dissolved in dimethyl sulfoxide (DMSO), triethylamine was added, and the reaction was carried out at 50°C for 24 hours. The resulting solution was dropped onto a glass plate and baked at 60°C for 24 hours to form a film, thereby obtaining a polybenzimidazole proton exchange membrane modified with a silane coupling agent.
[0012] The silane coupling agent is 3-isocyanate propyltrimethoxysilane or 3-chloropropyltrimethoxysilane, the molar ratio of the silane coupling agent to OHIPA is greater than 0 and less than 1, the molar mass of the silane coupling agent and triethylamine is the same, and the organic solvent for dissolving the silane coupling agent and OPBI-OHX can also be DMAc and DMF.
[0013] (3) The polybenzimidazole proton exchange membrane modified with silane coupling agent was heated at 80°C in 1 MH 2 SO 4 The membrane was immersed in water for 24 h, washed with water several times until the pH of the washing solution was neutral, and dried to obtain a polybenzimidazole proton exchange membrane containing a silicon-oxygen network structure, named cOPBI-OHX.
[0014] The cOPBI-OHX film was immersed in phosphoric acid and kept at 80°C for 24 hours to complete phosphoric acid doping. The membrane was taken out and the residual phosphoric acid on the surface was wiped off to obtain a phosphoric acid-doped polybenzimidazole high-temperature proton exchange membrane.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] (1) The introduction of a silicon-oxygen cross-linked network structure into polybenzimidazole can improve the antioxidant properties and tensile strength of the membrane and reduce the swelling rate of the acid-doped membrane;
[0017] (2) The silicon-oxygen network structure can slow down the loss of phosphoric acid in the acid-doped membrane and increase the service life of the proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the NMR spectrum of polybenzimidazole OPBI-OH30 containing ether bonds and phenolic hydroxyl functional groups;
[0019] Figure 2 The infrared spectra of polybenzimidazole OPBI-OH30 containing ether bonds and phenolic hydroxyl functional groups and silicon-oxygen cross-linked polybenzimidazole cOPBI-OH30. DETAILED DESCRIPTION
[0020] The present invention will be further described below with reference to the embodiments.
[0021] Example 1
[0022] (1) Preparation of PBI containing ether bonds and phenolic hydroxyl functional groups
[0023] In a nitrogen atmosphere, 2.1432 g DAB and 5.62 g P were added at 100 °C. 2 O 5 , 1.6482g OBBA and 0.7062g OHIPA were dissolved in 56.2g polyphosphoric acid (PPA) in sequence. After the drugs were completely dissolved, the temperature was raised to 160℃ for prepolymerization for 3h, and then polymerized at 200℃ for 10h until the solution was thick. The temperature was lowered to 70℃, 30ml phosphoric acid was added to hydrolyze the phosphate ester, and the polymer solution was poured into deionized water to precipitate solids. It was washed with boiling water several times until the pH of the washing solution was neutral, and dried at 80℃ for 24h to obtain 3.9g OPBI-OH30.
[0024] (2) Formation of silicon-oxygen network structure
[0025] Under nitrogen atmosphere, 2g OPBI-OH30 and 0.458g 3-isocyanate propyltrimethoxysilane were dissolved in 10ml dimethyl sulfoxide (DMSO), and 0.234g triethylamine was added. The reaction was carried out at 50℃ for 24h. The resulting solution was dropped onto a glass plate and dried at 60℃ to form a film, thereby obtaining a polybenzimidazole proton exchange membrane modified with a silane coupling agent. The membrane was heated at 80℃ in 1M H 2 SO 4 Soak in water for 24 hours, wash with water several times until the pH of the washing solution is neutral, and dry to obtain cOPBI-OH30 proton exchange membrane, the structure of which is as follows:
[0026]
[0027] The proton conductivity of the membrane is 66.36 mS·cm at 160°C. -1, immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 5%, the phosphoric acid absorption rate was 219.5%, and the tensile strength was 59.69MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 80.8%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, the remaining weight was measured to be 84.3% of the original mass, proving that the membrane has good chemical stability.
[0028] Example 2
[0029] The steps of this embodiment are basically the same as those of embodiment 1, except that the amounts of various monomers used in step (1) are different, DAB is 2.1432 g, P is 1.084 g, and 2 O 5 The amount of 3-isocyanatepropyltrimethoxysilane used in step (2) is 0.305 g, the amount of triethylamine used is 0.156 g, and the structure is as follows:
[0030]
[0031] The proton conductivity of the membrane is 63.42 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 6%, the phosphoric acid absorption rate was 225.61%, and the tensile strength was 57.42MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 79.6%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, the remaining weight was measured to be 81.9% of the original mass, proving that the membrane has good chemical stability.
[0032] Example 3
[0033] The steps of this embodiment are basically the same as those of embodiment 1, except that the amounts of various monomers used in step (1) are different, DAB is 2.1432 g, P is 1.084 g, and 2 O 5 The amount of 3-isocyanatepropyltrimethoxysilane used in step (2) is 0.158 g, the amount of triethylamine used is 0.078 g, and its structure is as follows:
[0034]
[0035] The proton conductivity of the membrane is 61.14 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 6%, the phosphoric acid absorption rate was 227.93%, and the tensile strength was 55.12MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 79.1%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, the remaining weight was measured to be 80.2% of the original mass, proving that the membrane has good chemical stability.
[0036] Example 4
[0037] The steps of this embodiment are basically the same as those of Example 2, except that the amount of 3-isocyanatepropyltrimethoxysilane used in step (2) is 0.158 g, and the amount of triethylamine used is 0.078 g. The structure is as follows:
[0038]
[0039] The proton conductivity of the membrane is 62.71 mS·cm at 160°C. -1 , immersed in 85% phosphoric acid at 80°C for 24 hours, the membrane swelling rate was 6%, the phosphoric acid absorption rate was 226.34%, and the tensile strength was 54.96MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 78.3%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, the remaining weight was measured to be 80.6% of the original mass, proving that the membrane has good chemical stability.
[0040] Example 5
[0041] (1) Preparation of PBI containing ether functional groups
[0042] Step (1) of this embodiment is exactly the same as step (1) of embodiment 1.
[0043] (2) Formation of silicon-oxygen network structure
[0044] Under nitrogen atmosphere, 2g OPBI-OH30 and 1.06g 3-chloropropyltrimethoxysilane were dissolved in 10ml dimethyl sulfoxide (DMSO) and reacted at 50℃ for 24h. The resulting solution was dropped onto a glass plate and dried at 60℃ to form a film to obtain a polybenzimidazole proton exchange membrane modified with a silane coupling agent. The membrane was heated at 80℃ in 1M H 2 SO 4Soak in water for 24 hours, wash with water several times until the pH of the washing solution is neutral, and dry to obtain cOPBI proton exchange membrane, the structure of which is as follows:
[0045]
[0046] The proton conductivity of the membrane is 38.4 mS·cm at 160°C. -1 The membrane was immersed in 85% phosphoric acid at 80°C for 24 hours. The membrane swelling rate was 5%, the phosphoric acid absorption rate was 186.5%, and the tensile strength was 59.84MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 76.2%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, and its remaining weight was measured to be 76.9% of the original mass ratio.
[0047] Comparative Example 1
[0048] The steps of this comparative example are exactly the same as step (1) in Example 1, and its structure is as follows:
[0049]
[0050] The proton conductivity of the membrane is 69.8 mS·cm at 160°C. -1 The membrane was immersed in 85% phosphoric acid at 80°C for 24 hours. The membrane swelling rate was 8%, the phosphoric acid absorption rate was 268.5%, and the tensile strength was 36.84MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 63.8%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, and its remaining weight was measured to be 70.6% of the original mass ratio.
[0051] Comparative Example 2
[0052] (1) PBI containing ether functional groups
[0053] In a nitrogen atmosphere, 2.1432 g DAB and 5.62 g P were added at 100 °C. 2 O 5 , 2.3544g OBBA were dissolved in 56.2g polyphosphoric acid (PPA) in turn, and after the drugs were completely dissolved, the temperature was raised to 120℃ for prepolymerization for 2h, and then polymerized at 160℃ for 4h until the solution was thick. The temperature was lowered to 70℃, and the polymer was poured into deionized water, and washed several times with deionized water until the pH of the washing solution was adjusted to neutral with sodium bicarbonate, and then dried at 80℃ for 24h to obtain 3.8g OPBI,
[0054] (2) Formation of silicon-oxygen network structure
[0055] Under nitrogen atmosphere, 2g OPBI and 1.55g 3-isocyanate propyltrimethoxysilane were dissolved in 10ml dimethyl sulfoxide (DMSO) and reacted at 70℃ for 24h. The resulting solution was dropped onto a glass plate and dried at 60℃ to form a film to obtain a polybenzimidazole proton exchange membrane modified with a silane coupling agent. The membrane was heated at 80℃ in 1M H 2 SO 4 Soak in water for 24 hours, wash with water several times until the pH of the washing solution is neutral, and dry to obtain cOPBI proton exchange membrane, the structure of which is as follows:
[0056]
[0057] The proton conductivity of the membrane is 35.8 mS·cm at 160°C. -1 The membrane was immersed in 85% phosphoric acid at 80°C for 24 hours. The membrane swelling rate was 5%, the phosphoric acid absorption rate was 166.5%, and the tensile strength was 60.28MPa. After being placed at 100°C for 120 hours, the phosphoric acid retention rate was 74.5%. The membrane was immersed in Fenton's reagent (4ppm Fe 2+ , 3% H 2 O 2 ), placed at 80°C for 96 hours, and its remaining weight was measured to be 76.1% of the original mass ratio.
Claims
1. A high temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole, characterized in that: The proton exchange membrane structure is as follows:
2. A method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 1, characterized in that: The preparation method comprises the following steps: firstly polymerizing 3,3'-diaminobenzidine, 4,4'-diphenyl ether dicarboxylic acid and 5-hydroxyisophthalic acid to form a polybenzimidazole main chain containing ether bonds and phenolic hydroxyl groups, then grafting a silane coupling agent onto the polybenzimidazole main chain, and finally performing film formation and acid catalysis treatment to obtain a silicon-oxygen cross-linked polybenzimidazole proton exchange membrane.
3. The method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 2, characterized in that: The preparation method steps are as follows: (1) Preparation of polybenzimidazole containing ether bonds and phenolic hydroxyl functional groups Under a nitrogen atmosphere at 100°C, 3,3'-diaminobenzidine, phosphorus pentoxide, 4,4'-diphenyl ether dicarboxylic acid and 5-hydroxyisophthalic acid were dissolved in polyphosphoric acid in sequence, and after being completely dissolved, the temperature was raised to 160°C for prepolymerization for 3 hours, and the solution was polymerized at 200°C until the solution was solid; the temperature was lowered to 70°C, phosphoric acid was added to hydrolyze the phosphate ester, and the polymer solution was poured into deionized water to precipitate solids, which were washed with boiling water until the pH of the washing solution was neutral, and dried at 80°C for 24 hours to obtain a polybenzimidazole containing ether bonds and phenolic hydroxyl functional groups, named OPBI-OHX, where X is the total molar percentage of OHIPA to OBBA and OHIPA, 0<X<50; (2) Formation of silicon-oxygen network structure Under nitrogen atmosphere, OPBI-OHX and silane coupling agent were dissolved in dimethyl sulfoxide, triethylamine was added, and the reaction was carried out at 50°C for 24 hours. The obtained solution was dropped onto a glass plate and dried at 60°C for 24 hours to form a film, thereby obtaining a polybenzimidazole proton exchange membrane modified with a silane coupling agent. (3) The polybenzimidazole proton exchange membrane modified with a silane coupling agent was immersed in 1 M H2SO4 at 80°C for 24 h, washed with water until the pH of the washing solution was neutral, and baked at 80°C for 24 h to obtain a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole, named cOPBI-OHX.
4. The method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 3, characterized in that: In step (1), the molar ratio of 3,3'-diaminobenzidine to the total molar ratio of 4,4'-diphenylether dicarboxylic acid and 5-hydroxyisophthalic acid is 1:
1.
5. The method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 3, characterized in that: In step (1), the mass of phosphorus pentoxide is 8-15% of the mass of polyphosphoric acid.
6. The method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 3, characterized in that: In step (2), the silane coupling agent is 3-isocyanate propyltrimethoxysilane or 3-chloropropyltrimethoxysilane.
7. The method for preparing a high-temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 3, characterized in that: In step (2), the molar ratio of the silane coupling agent to 5-hydroxyisophthalic acid is greater than 0 and less than 1, and the molar ratio of the silane coupling agent to triethylamine is 1:
1.
8. An application of a high temperature proton exchange membrane based on silicon-oxygen cross-linked polybenzimidazole according to claim 1, characterized in that: The proton exchange membrane is used for the proton exchange membrane of a high-temperature proton exchange membrane fuel cell.
Citation Information
Cited By
Hydroxyl-containing modified polybenzimidazole proton exchange membrane and preparation method thereof
CN120365559A
High-oxidation-resistance polybenzimidazole proton exchange membrane as well as preparation method and application thereof
CN121378746A
A high-oxidation-resistance polybenzimidazole proton exchange membrane, a preparation method and application thereof
CN121378746B
Cross-linking type polybenzimidazole proton exchange membrane with oxidation resistance and high proton conductivity and preparation method of cross-linking type polybenzimidazole proton exchange membrane
CN121949791A